Obravnava besedil - Krajnc Ivič, Mira (Slavistična revija, 2020)
Texts that display common prototypical characteristics are often grouped into text types or genres. Genres are the result of habitual language and behavioural activities within the communicative field of a specific discursive community. The definition of a genre derives from the complementary model of text definitions. Unlike genres, text types are formed based on language infrastructure; they are not part of systematic text grouping (classification and typologisation). Knowledge of genres is crucial to participating in social processes.
Keywords: besedila; besedilne vrste; besedilni tipi; besediloslovje; classification; klasifikacija; text linguistics; text types; texts; tipologizacija; typologisation